2006
DOI: 10.1090/s0033-569x-06-01002-5
|View full text |Cite
|
Sign up to set email alerts
|

Viscous flow due to a shrinking sheet

Abstract: Abstract. The viscous flow induced by a shrinking sheet is studied. Existence and (non)uniqueness are proved. Exact solutions, both numerical and in closed form, are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
335
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 599 publications
(357 citation statements)
references
References 11 publications
21
335
0
1
Order By: Relevance
“…The exact solution in this work provides a general formulation for both the stretching sheet (Crane problem [2]) and the shrinking sheet (Miklavčič and Wang problem [25]). In addition, the current results extend the sheet velocity from a pure linear velocity to a more general condition with a constant wall translating velocity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact solution in this work provides a general formulation for both the stretching sheet (Crane problem [2]) and the shrinking sheet (Miklavčič and Wang problem [25]). In addition, the current results extend the sheet velocity from a pure linear velocity to a more general condition with a constant wall translating velocity.…”
Section: Resultsmentioning
confidence: 99%
“…This new type of shrinking sheet flow is essentially a backward flow as discussed by Goldstein [26]. Physically, there are two conditions that the flow towards the shrinking sheet is likely to exist: whether an adequate suction on the boundary is imposed (Miklavčič and Wang [25]) suction is required to maintain the flow over a shrinking sheet. Problems of boundary layer flow over shrinking sheets with mass transfer have been studied by Fang [27], Fang et al [28], Fang and Zhang [29] and Fang et al [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang [5] first pointed out the flow over a shrinking sheet when he was working on the flow of a liquid film over an unsteady stretching sheet. The existence and uniqueness of steady viscous flow due to a shrinking sheet was established by Miklavcic and Wang [6] and they concluded that for some specific value of suction at the sheet, dual solutions exist and also in certain range of value of suction, no boundary layer solution exists. Fang and Zhang [7] recently investigated the heat transfer characteristics of the shrinking sheet problem with a linear velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The flow due to a shrinking sheet has its important applications in industries such as manufacturing of polymer sheets, filaments and wires. The shrinking sheet phenomenon with a suction effect was first investigated by Miklav i and Wang [3]. Since then, there have been quite a number of studies which are related to permeable shrinking flow, either in different fluid media or different boundary conditions.…”
Section: Introductionmentioning
confidence: 99%